Hipertensi Sebagai Determinan Utama untuk Peningkatan Risiko Stroke pada Populasi Penduduk di Daerah Pesisir - Herpan Syafii Harahap; Ilsa Hunaifi; Ghalvan sahidu; Stephanie Elizabeth Gunawan; Setyawati Asih Putri; Ni Nyoman Ayu Susilawati; Baiq Hilya Kholida (Faculty of Medicine Universitas Mataram, 2022)
Hypertension is the main determinant of stroke in the population in coastal areas. This is mainly related to the pattern of daily high sodium salt intake that is characteristic for the population in these areas. Chronic consumption of sodium salt > 5 grams/day will increase the risk of hypertension. Since marine fish naturally have high levels of sodium and its level will be increased during processing and packaging, chronic consumption of marine fish can be considered as a risk factor for hypertension and stroke as well. Pathophysiologically, high sodium levels for a long period may cause dysfunctional of pressure natriuresis, a condition that underlies hypertension. The hypertension itself will then induce the structural changes of blood vessels wall in the brain that support the occurrence of stroke. Since economically, the use of sodium salt for the preservation process, taste modification, and color and texture modification of seafood products, including marine fish, is more affordable, while the availability of substitutes for sodium salt for these purposes is relatively expensive and not always available, educational program for coastal communities related to daily sodium salt consumption control as an effort to prevent stroke are a distinct challenge for local health authorities.